1999
DOI: 10.1007/bf02434817
|View full text |Cite
|
Sign up to set email alerts
|

Age-related peculiarities of heart rate in intact and sympathectomized rats injected with atropine

Abstract: Atropine induced various changes in the heart rate in intact rats of various ages. In sympathectomized animals, changes in heart rate variability were less pronounced. Atropine blocked the inhibition of cardiac activity induced by electrical stimulation of the vagus nerve.Key Words: rat; heart rate; sympathectomy; atropine," vagus nerve Vagotomy sharply increases heart rate (HR) in dogs and cats [7]. Atropine, a nonspecific muscarinic receptor (MR) blocker, induces similar effects [2,8,9,11]. Experimental data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…Previous studies showed that nonselective blockade of muscarinic AChR had no effect on heart rate [2]. Administration of selective antagonists of muscarinic M 1 and M 2 AChR was not accompanied by significant increase in heart rate.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Previous studies showed that nonselective blockade of muscarinic AChR had no effect on heart rate [2]. Administration of selective antagonists of muscarinic M 1 and M 2 AChR was not accompanied by significant increase in heart rate.…”
Section: Resultsmentioning
confidence: 96%
“…The short-term decrease in BP after muscarinic AChR blockade reflects the vasoconstrictor effect of acetylcholine. Published data show that administration of atropine prevents bradycardia during electrostimulation of the vagus nerve [2,3]. Selective blockade of 1 of 3 subtypes of muscarinic AChR did not prevent the decrease in HR during stimulation of the right vagus nerve.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It was hypothesized that the chronotropic effect of the vagus nerve includes several components [2,9]. Nonselective blockade of M-ChR with atropine and vagotomy have various effects on the heart [3,6].…”
mentioning
confidence: 99%